Synchronized by photoperiod: Shedding light on flowering seasonality in Acrocomia species (Arecaceae) - Catherine Jeanne Marguerite Meyer; Cláudio Emanuel Magaton; Thomas Hilger; Kalcida Naomi Kuki; Sérgio Yoshimitsu Motoike; Georg Cadisch (PLoS ONE, 2026)
Interest in the oilseed palm genus Acrocomia has grown due to its potential as a sustainable alternative to the African oil palm ( Elaeis guineensis ). Recent research has focused on genetic resource development, and oil yield and quality, and applying this knowledge toward domestication. However, major knowledge gaps remain regarding yield formation, particularly the understanding of flowering phenology. In addition, the environmental drivers regulating its flowering phenology remain unclear. While flowering is often assumed to be triggered by the onset of the rainy season, evidence from different regions suggests that this cue is unreliable. This study aimed to determine the climatic and photoperiodic drivers of Acrocomia flowering seasonality and to assess variation among accessions of A. totai , A. intumescens and A. aculeata from diverse South American origins. We monitored six Acrocomia accessions cultivated under identical conditions in the Active Germplasm Bank of Acrocomia (BAG-Macaúba) in Araponga, Brazil, over three flowering seasons (2019–2021). Using circular statistics, seasonal decomposition, and moving-window correlations, we analyzed relationships between flowering patterns and temperature, precipitation, solar radiation, and photoperiod. The flowering exhibited strong seasonality from September to January, with synchronous patterns across seasons. Photoperiod was identified as the predominant factor associated with flowering timing, while precipitation and temperature showed weaker and less consistent links, contributing only to minor interannual fluctuations. These results suggest that photoperiod may act as a primary seasonal cue for Acrocomia lowering, while episodic climatic variations act as secondary modukators. This improved comprehension facilitates the formulation of strategies for pollination management, genotype selection, and yield stability in prospective Acrocomia cultivation and breeding programs.